The Islamic Financing on Macroeconomic Stability in Indonesia - Aini, Marro (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
The objective of this study is to examine the function of Islamic finance in fostering macroeconomic stability in Indonesia. Specifically, it will scrutinize the stability of Islamic banks, its effects on micro, small, and medium enterprises (MSMEs), and its impact on economic growth and inflation. Employing a qualitative research approach, data were gathered by means of document analysis, encompassing books, scholarly publications, and institutional reports. The results demonstrate that Islamic banks, which employ profit-sharing and asset-backed financing structures, have higher levels of stability in comparison to conventional banks, therefore mitigating the likelihood of financial catastrophes. Islamic finance has profoundly facilitated the expansion of MSMEs by offering cost-effective, interest-free lending, therefore augmenting their productivity and economic contributions. Furthermore, Islamic finance promotes consistent economic expansion by prioritizing investments in tangible assets in industry areas such as agriculture and manufacturing. Although it suppresses speculative activity, its effect on inflation is inconclusive, as further growth of micro, small, and medium enterprises (MSMEs) may have upward influence on pricing. In conclusion, the study highlights that Islamic finance contributes to Indonesia's macroeconomic stability by strengthening Islamic banks, promoting MSME development, and fostering balanced economic growth. The data shows a consistent rise in the contribution of MSMEs to Indonesia's GDP from 57.08% in 2017 to 61.90% in 2022, underscoring their increasing significance in the national economy. This upward trend highlights the growing role of MSMEs in economic development.